2019
DOI: 10.1111/ajsp.12384
|View full text |Cite
|
Sign up to set email alerts
|

Western and East Asian sociocultural learning models: Evidence from cross‐cultural and immigrant research

Abstract: We review Li's research and theory of cultural learning models in light of Chirkov's (2019) theory of sociocultural models that draw on previous theories and research across social sciences. We recast Li's models as sociocultural learning models (SCLMs) by incorporating Chirkov's three emphases: (a) the inseparability between the social and the cultural, (b) the public versus individuals' internalization of SCLMs and their mutual enforcement, and (c) collective intentionality and intersubjectivity as embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Li and Yamamoto’s article in this issue (Li & Yamamoto 2020 ) and the first author’s previous publications (Li, 2004, 2012) serve as illustrations of applications of the cultural model approach to the cross‐cultural analysis of the cultural learning models in China and the United States. This same logic has been applied to the understanding of mental pathology and related inquiries in clinical psychology (Chentsova‐Dutton & Ryder, 2020).…”
Section: Sociocultural Psychology and The Theory Of Sociocultural Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li and Yamamoto’s article in this issue (Li & Yamamoto 2020 ) and the first author’s previous publications (Li, 2004, 2012) serve as illustrations of applications of the cultural model approach to the cross‐cultural analysis of the cultural learning models in China and the United States. This same logic has been applied to the understanding of mental pathology and related inquiries in clinical psychology (Chentsova‐Dutton & Ryder, 2020).…”
Section: Sociocultural Psychology and The Theory Of Sociocultural Modelsmentioning
confidence: 99%
“…For nearly 20 years, Li has successfully used the cognitive anthropological version of the theory of cultural models in her research (Li, 2001, 2002, 2003). Subsequently, she has summarised her studies on cross‐cultural comparisons of these cultural learning models in her book (Li, 2012). Even though Li’s research has been based on solid theoretical and empirical foundations, she and her colleague understand that gaps exist in their theoretical conceptualisation and that these gaps must be addressed for them to successfully continue to explore further the psychosociocultural mechanisms of teaching and learning and the cross‐cultural differences in these processes.…”
Section: Contributions To This Issuementioning
confidence: 99%
“…Chirkov’s insistence on the inseparability of the cultural and the social is noteworthy (also see Li & Yamamoto, this issue). I agree with this fundamental proposition that the cultural and the social are ontologically inseparable, but I would like to retain an analytical (or conceptual) distinction between the two.…”
Section: The Cultural the Social And The Natural In Psychologymentioning
confidence: 99%
“…Li and Yamamoto (this issue) provide an excellent illustration of how the seemingly universal process of internalisation‒externalisation is at once a mechanism for cultural diversity and its maintenance in the context of mother‒child interaction. After reviewing Li and Yamamoto’s empirical research on cultural differences in Western and East Asian learning processes, their reported a highly informative discourse analysis of European American and Chinese American mother‒child interactions, expertly illustrating how intentionality and intersubjectivity play out in the enactment, transmission, and reinforcement of SCMs of learning socially in situ.…”
Section: Intentionality Intersubjectivity and Constitution Of Sociomentioning
confidence: 99%
See 1 more Smart Citation